Influence of Fermentation and Milling Processes on the Nutritional and Bioactive Properties of Pistachio-Based Beverages - Di Renzo, Tiziano (2025)
The study aimed to evaluate how different production methods and fermentation processes using two different lactic acid bacteria (LAB) affect the chemical composition and bioactive properties of pistachio beverages. The beverages were prepared with two varieties of pistachios, one from Argentina and the other from Italy. The pistachios were processed with two technologies: a domestic processor and a colloidal mill. For the fermentation, pistachio beverages were inoculated with two different LAB strains and incubated at 28 ◦C for 24 h. The beverages were analyzed for proximal composition (including protein, fat, fiber, and minerals) and bioactive properties such as antioxidant activity, angiotensinconverting enzyme inhibition (ACE-I), and dipeptidyl peptidase-4 inhibition (DPP-4). The colloidal milling allowed the inclusion of the whole pistachio nut, resulting in beverages with higher solid content and no waste. Beverages treated with colloidal milling exhibited higher acidity, improved microbial fermentation performance, and generally showed higher bioactivity compared to those obtained by the domestic processor. Bioactivity varied according to the pistachio variety, the processing method and LAB strains used. Lactic acid bacteria fermentation decreased antioxidant properties of the beverages by ~40% but improved anti-hypertensive and hypoglycaemic activities. Fermented pistachio-based beverages showed promising health-promoting properties, indicating their potential as functional foods.